INFLUENCE OF ELEVATED CO₂ ON AGRICULTURAL SYSTEMS: A REVIEW - Pedroso, Rafael Munhoz; Dourado Neto, Durval (REVISTA DE AGRICULTURA, 2020)
Agriculture constitutes the second largest biome on Earth’s surface and is responsible for a third of the world’s net primary production. Carbon dioxide (CO2) is directly linked to the primary production of ecosystems through its major role in photosynthesis. CO2 levels on Earth’s atmosphere have increased substantially since the Industrial Revolution and increase at a rate of 3.2 ppm per year. Along with such rises, shifts in precipitation patterns and global annual temperature averages have occurred, which might affect food production worldwide. The present work aimed at assessing how elevated CO2 concentrations affect net accumulation of carbon in this biome, increasing net photosynthesis and nitrogen- and water-use efficiency. Interactions among elevated atmospheric CO2, temperature and precipitation – major climate parameters driving current changes - are discussed, as well as means by which crop physiological responses to elevated CO2 can help mitigate some of the deleterious effects predicted in many agricultural systems worldwide